Dimensional Changes of Cross-Laminated Timber Basement Walls Under Ambient Humidity Variation - Fernanda Bezerra Tomaduci Imamura; Yuxiang Chen; Lijun Deng; Ying Hei Chui (BioResources)
Advancements in cross-laminated timber (CLT) applications have introduced the potential to use it as an alternative to reinforced concrete in basement construction. Understanding dimensional stability is crucial to ensure the reliability and safety of CLT in below-grade environments. An experimental CLT basement was constructed in Edmonton, Canada, and monitored over a period of two years. Field measurements were analyzed to estimate the dimensional changes and understand the deformation modes of the CLT panels resulting from changes in boundary conditions. A supporting laboratory experiment with specimens made from single pieces of dimensional lumber was conducted to establish a basis for comparing field-measured dimensional changes in CLT and determining the effects of cross-lamination on swelling and shrinkage coefficients. The average swelling and shrinkage coefficients calculated for CLT were approximately twice as large as the longitudinal and 20 times smaller than the transverse coefficients obtained from the laboratory experiments on solid wood specimens, indicating the influence of cross-lamination on these coefficients. Four deformation modes were identified based on measurements from field-installed strain gauges. The study provides new insights into the impact of water ingress on the swelling coefficient and the effects of different drying conditions on the shrinkage coefficients of CLT.